Morphological sexual characteristics of the giant water bug Lethocerus indicus (Lepeletier et Serville, 1825) and their habitats in Vietnam - Manh, Vu Quang; Bich Lam, Le Thi (Academia Journal of Biology, 2012)
Studies on morphological sexual systematical characteristics of the giant water bug L. indicus and their habitats were carried out throughout Vietnam, in the period of 2000-2010. It is not recorded a special sexual difference in morphological characteristics and color of the giant water bug. The male’s body measurements are smaller than those of the female, 70.3 ± 0.25 × 26.3 ± 0.3 mm and 78.64 ± 0.33 × 28.63 ± 0.06 mm, respectively. The male genital capsule, i.e. phallobase, aedeagus, diverticullum and parameres, as well as the female genital capsule, i.e. gonapophysis, valve and anal cone, of the giant water bug were described. These are the most cleared characteristics in identification the male and the female. The proportion between a length and width of the last abdomen segment of the bug is an important mark in recognizing a male and female; and it was indicated 2.66 and 2.12, respectively. In Vietnam, the habitats of the giant water bug L. indicus are ranged to the following order: 1. Water rice fields with water level < 50 cm with 81% of the total specimens obtained; 2. Ponds and lakes with water level > 50 cm, 14%; 3. Rivers and streams, 3%; and 4. Habitats out of water, 2%.